2019
DOI: 10.1155/2019/2174562
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Transverse Effective Bending Rigidity of Shield Tunnels

Abstract: The uniform rigidity ring model is commonly used to design the segmented structures of shield tunnels. However, model tests have been primarily used to study the transverse effective rigidity ratio η with a concentrated force, which is notably different from realistic loading patterns. To obtain more reasonable η values, in this study, tests were performed with a concentrated load on an experimental bench and with a realistic loading pattern in sandy soil in a rigid steel tank. Three types of segmental ring mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Therefore, the effective stiffness ratio of tunnel η (η ≤ 1) is introduced to reflect the weakening effect of segment joints on the tunnel stiffness, i.e., the equivalent stiffness of the tunnel is ηEI, where EI is the bending stiffness of the homogeneous tunnel before stiffness reduction. Some studies [24][25][26][27][28] demonstrated that the value of η is related to the soil conditions, the form of the segment joints, and the manner of segment assembly. In this study, the value of η = 0.75 is adopted, referring to the above studies.…”
Section: Constitutive Model and Parametersmentioning
confidence: 99%
“…Therefore, the effective stiffness ratio of tunnel η (η ≤ 1) is introduced to reflect the weakening effect of segment joints on the tunnel stiffness, i.e., the equivalent stiffness of the tunnel is ηEI, where EI is the bending stiffness of the homogeneous tunnel before stiffness reduction. Some studies [24][25][26][27][28] demonstrated that the value of η is related to the soil conditions, the form of the segment joints, and the manner of segment assembly. In this study, the value of η = 0.75 is adopted, referring to the above studies.…”
Section: Constitutive Model and Parametersmentioning
confidence: 99%
“…Empirical methods and theoretical analyses are used to predict surface settlement and stratum movements caused by shield tunnelling [24,25]. Model tests also play an important role in investigating mechanical behaviour of shield tunnelling [26][27][28][29]. Meanwhile, in order to obtain the real data of shield tunnel, construction field monitoring also has been adopted [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the range of the effective ratio of the transverse bending rigidity value is between 0.09 and 0.23 under straight-jointed condition and 0.30 and 0.80 under stagger-jointed condition. Zheng et al [24] also adopted polyethylene and aluminium wire to fabricate the shield tunnel models, and the effective rigidity ratios of the tunnel were investigated through testing the model under the concentrated load and realistic loading pattern in sandy soil. Taking the Shanghai Yan-Jiang Tunnel as an example, Li et al [25] analysed the influence of buried depth on the effective ratio of the transverse bending rigidity and found that the buried depth has a great influence on η. Feng et al [26] carried out prototype tests on segmental lining structure for shield tunnel with a large cross section and attained the variation pattern of η and ξ with load conditions; the experiment also showed that as the section increases, η increases while ξ decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies mainly focus on the transverse effective bending rigidity ratio in the elastic stage. For example, elastic materials are always used in model tests [22][23][24]. However, the damage process of the material of segment rings as the load increases can also conversely influence the value of the transverse effective bending rigidity ratio.…”
Section: Introductionmentioning
confidence: 99%